Investigation of functionalised nanoplatforms using branched-ligands with different chain lengths for glioblastoma targeting. (6th October 2022) - Wang, Siqi; Yang, Zhongzhen; Yang, Chunyan; Chen, Jinxia; Zhou, Lin; Wu, Yong; Lu, Runxin
Abstract: Glioblastoma, a common malignancy of the central nervous system, is the most destructive type of brain cancer. Clinical treatment remains a major challenge due to high infiltrative growth and the presence of the blood brain barrier (BBB). Therefore, advanced nanoplatforms that can efficiently cross the BBB and target brain tumours are highly desired. Compared with the targeting efficiency of single ligand nanoplatforms, dual targeting nanoplatforms may lead to better and controllable malignant cell selectivity. In this study, based on our previous research of branched ligands, we finally determined to use tri-branched glucose and two-branched biotin as targeting molecules, and in order to explore the synergetic-targeting capabilities and the mutual influence between the length of the two ligands, we designed three kinds of two-branched biotin ligands with a different linker and co-modified with the tri-branched glucose ligands on the surface of liposomes. The results of in vivo and in vitro experiments showed the (Glu3 +Bio2 )-2-Lip can exert the greatest synergistic targeting ability. The application of branched ligands, the dual-targeting design concept, and the exploration of the interaction between the chain lengths of the two ligands have brought new ideas and new methods for the targeted therapy of glioma.